Communication Rhetoric as a Tool for Personal Branding:: The CEO’s Role in Developing Global Youth Ambassadors - Salsabila, Alya Dwi (Indonesian Research Journal on Education, 2025)
The purpose of this study is to see how the rhetorical analysis on the formation of Hofyan Nazaki's personal branding as the Chief Executive Officer (CEO) of the Global Youth Ambassador. The ability to communicate is very important when correlated with the development of personal branding. In general, speaking skills show a person's credibility because they are considered more likely to succeed in their career life. Rhetoric is a practical art in persuasion by focusing on managing arguments, drafting ideas, using language, and procedures for delivering speech. Then how communication rhetoric can play an important role in the formation of personal branding so that it is able to build a good image in running social life, in this study the author wants to find out and analyze the influence of communication rhetoric in the formation of personal branding Hofyan Nazaki as Chief Executive Officer (CEO) of Global Youth Ambassador. The method used in this study is qualitative descriptive. Primary data sources were obtained from interviews with the Chief Executive Officer (CEO) of the Global Youth Ambassador. Secondary data is sourced from data obtained through Instagram @globalyouth.amb, documents or literature that support primary data. Based on the results of research and data collection, it can be concluded that communication that is carried out well, beautifully, and systematically can form a person's personal branding. By using communication techniques with the principles of the 5 cannons of rhetoric, a person can more easily persuade and speak well and effectively. In forming a person's personal branding, good and effective communication is needed.